2016
DOI: 10.1093/rfs/hhw030
|View full text |Cite
|
Sign up to set email alerts
|

Law and Finance Matter: Lessons from Externally Imposed Courts

Abstract: This paper provides novel evidence on the real and financial market effects of legal institutions. Our analysis exploits persistent and externally imposed differences in court enforcement that arose when the U.S. Congress assigned state courts to adjudicate contracts on a subset of Native American reservations. Using area-specific data on small business lending, we find that reservations assigned to state courts, which enforce contracts more predictably than tribal courts, have stronger credit markets. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 76 publications
2
60
0
1
Order By: Relevance
“…Brown, Cookson, and Heimer (2017) find that several key indicators of subsequent banking market development are significantly greater on reservations with state courts, including the propensity for banks to extend credit and the extent of bank branching activity. For example, their estimates suggest state court jurisdiction led to approximately 20 percent more community bank branches per capita.…”
Section: Reservation Financial Development Before and After Public Lamentioning
confidence: 94%
See 3 more Smart Citations
“…Brown, Cookson, and Heimer (2017) find that several key indicators of subsequent banking market development are significantly greater on reservations with state courts, including the propensity for banks to extend credit and the extent of bank branching activity. For example, their estimates suggest state court jurisdiction led to approximately 20 percent more community bank branches per capita.…”
Section: Reservation Financial Development Before and After Public Lamentioning
confidence: 94%
“…Brown, Cookson, and Heimer (2017 , Table 1) use hand-collected 9 The 1968 Indian Civil Rights Act also allowed for retrocession of PL280 authority, but the process for retrocession of state court authority to tribal courts is difficult to initiate by tribes. Thus, there were few instances where tribal court authority was regained.…”
Section: Reservation Financial Development Before and After Public Lamentioning
confidence: 99%
See 2 more Smart Citations
“…Similar concerns have been raised about access to and usage of consumer credit, including bankcards, for American Indians and American Indian communities-"America's domestic emerging market" (Clarkson 2009: 287)for which research has been particularly scarce even though undersupply of credit had been identified as a key obstacle to economic progress of American Indian reservations (see, e.g., Community Development Financial Institutions Fund 2001, Parker 2012, Brown et al 2015. 3 Using SCF data, Crook (1996: 482) …”
mentioning
confidence: 94%